Patient Records: from Single Events to Elements for Health Planning - Pisanelli, D. M.; Ricci, F. L. (Methods of Information in Medicine, 1994)
Data collected in patient records are not only the kernel of a ward information system, but also the groundwork for planning and evaluating services in health care. The aim of this study was to analyze the problem of aggregate data generation starting from separate items in patient records. After describing the different uses of patient record data, we outline the process which generates aggregate data starting from individual records. This process leads to the definition of the “view on aggregation” as an intermediate step between patient records and aggregate data.A simplified schema is presented based on the Entity-Relationship model representing a conceptual model of the integration of aggregate data and patient record items. Finally, the role is discussed of automation in this process and the perspectives for its implementation.
Keywords: Patient Records; Health Care Planning; Statistical Databases